2020
DOI: 10.1128/iai.00545-20
|View full text |Cite
|
Sign up to set email alerts
|

Host and Bacterial Glycolysis during Chlamydia trachomatis Infection

Abstract: The obligate intracellular pathogen Chlamydia trachomatis is the leading cause of non-congenital blindness and causative agent of the most common sexually transmitted infection of bacterial origin. With a reduced genome, C. trachomatis is dependent on its host for survival, in part due to a need for the host cell to compensate for incomplete bacterial metabolic pathways. However, relatively little is known regarding how C. trachomatis is able to hijack host cell metabolism. In this study, we show that two host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…However, all other known mechanisms are lacking. Alternatively, WGS analyses have revealed that Chlamydia species contain genes for a complete glycolysis pathway (except for hexokinase, utilising hexose phosphate transporter to uptake host glucose-6-phosphate instead) and sodium-driven oxidative phosphorylation to generate its own ATP for energy or nucleic acid synthesis) and a hexose phosphate transporter, allowing Chlamydia to use glucose-6-phosphate as an energy source ( Liang et al., 2018 ; Sigalova et al., 2019 ; Ende and Derré, 2020 ). However, this process would still depend on ADP availability from nucleotide uptake or interconversion.…”
Section: Chlamydial Genome Organisation and Content: Variability With...mentioning
confidence: 99%
“…However, all other known mechanisms are lacking. Alternatively, WGS analyses have revealed that Chlamydia species contain genes for a complete glycolysis pathway (except for hexokinase, utilising hexose phosphate transporter to uptake host glucose-6-phosphate instead) and sodium-driven oxidative phosphorylation to generate its own ATP for energy or nucleic acid synthesis) and a hexose phosphate transporter, allowing Chlamydia to use glucose-6-phosphate as an energy source ( Liang et al., 2018 ; Sigalova et al., 2019 ; Ende and Derré, 2020 ). However, this process would still depend on ADP availability from nucleotide uptake or interconversion.…”
Section: Chlamydial Genome Organisation and Content: Variability With...mentioning
confidence: 99%
“…Either 2 μg/ml of DOX or 5 μg/ml of AZM inhibits C. trachomatis induced host metabolic activation as well as production of progeny, whereas C. trachomatis still survived and hence activated host metabolism under treatment with therapeutic serum concentration of AZM. Since C. trachomatis fundamentally needs host cell metabolites for its replication, it manipulates host cell glycolysis and mitochondria (Chowdhury et al, 2017;Shima et al, 2018Shima et al, , 2021Kurihara et al, 2019;Ende and Derré, 2020;Maffei et al, 2020;Rajeeve et al, 2020). Therefore, we suggest that the suppression of host metabolism enhanced by C. trachomatis is also an important factor for treatment of C. trachomatis infections.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, a recent study demonstrated that three glycolytic enzymes, aldolase A, pyruvate kinase (PK) and lactate dehydrogenase (PDH), were enriched at the inclusion membrane, and the former was proven to be important for inclusion formation and bacterial development. The authors suggested that recruitment of host glycolytic enzymes at the inclusion membrane could be a way by which the bacteria have easier access to ATP or small metabolites produced through the glycolytic pathways, or to nucleotides produced by the pentose phosphate pathway (15). GNE-140 treatment might affect the localization of these enzymes, so that even if the intermediates of glycolysis are still being made in the presence of the drug, they might have lost in accessibility for the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we addressed whether infected cells modified their glycolysis or OxPhos capacities, and at what stage of the infectious cycle were these host pathways critical for optimal bacterial replication. Past work had shown that glycolysis was important for bacterial development (14,15). However, these studies were conducted mainly in cancer-derived cell lines, which are known to have an abnormal metabolism.…”
Section: Introductionmentioning
confidence: 99%